Research-based planning for public libraries increasing relevance in the digital age - Matthews, Joseph R. (Libraries Unlimited, an inprint of ABL-CIO, LLC, 2013)
"This book will help public library administrators, managers, and board members to better plan, strategize, and understand their communities, enabling public libraries to become dynamic, proactive institutions"-- Provided by publisher